2020
DOI: 10.1096/fba.2019-00080
|View full text |Cite
|
Sign up to set email alerts
|

Low bone mineral density due to secondary hyperparathyroidism in theGlatmTg(CAG‐A4GALT)mouse model of Fabry disease

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Moreover, in our patient carrying this variant we also observed a 50% reduction in enzymatic activity, when compared to control patients. Clinically this female patient showed some clinical features that are known to be associated with Fabry disease, such as bone involvement [34]. Indeed, secondary osteoporosis can be associated with decreased intestinal vitamin D absorption, which is in turn associated with several mechanisms that precede the onset of Fabry disease.…”
Section: Discussionmentioning
confidence: 77%
“…Moreover, in our patient carrying this variant we also observed a 50% reduction in enzymatic activity, when compared to control patients. Clinically this female patient showed some clinical features that are known to be associated with Fabry disease, such as bone involvement [34]. Indeed, secondary osteoporosis can be associated with decreased intestinal vitamin D absorption, which is in turn associated with several mechanisms that precede the onset of Fabry disease.…”
Section: Discussionmentioning
confidence: 77%
“…In one previous study the authors tried to elucidate the pathomechanism of calcium-phosphate disturbances in patients with FD using a mouse model GlatmTg (CAG-A4GALT). The study results showed a relationship between hypercalcemia and hypercalciuria and secondary hyperthyroidism (27). This may suggest that patients with FD are at increased risk of accelerated bone resorption and osteomalacia (28).…”
Section: Wwwirdrjournalcommentioning
confidence: 83%
“…However, commercially available antibodies, ab206655 and ABN182 showed unacceptable results. These antibodies have been used for Western blotting and immunohistochemistry in many studies (26)(27)(28)(29)(30)(31)(32)(33)(34), and have caused the idea that Cyp27b1 is present in many tissues other than the kidney. In general, choosing an inappropriate antibody is a major hindrance in advancing research, but in the case of Cyp27b1 antibodies, inappropriate antibodies have been overlooked so far.…”
Section: Discussionmentioning
confidence: 99%